Development of SETS E-Module Integrated with POE Model for Science Learning - Insih Wilujeng; Tri Suci Yolanda Putri (Journal of Educational Science and Technology (EST), 2020)
This research developed Science, Environment, Technology, Society (SETS) e-module integrated with predict, observe, explain (POE) model on the subject matter of Earth Layer and Its Dynamics for grade VII students. This study aimed to reveal i) the feasibility of the developed e-module for grade VII students, and ii) the practicality of the developed e-module and its dynamics. This is a developmental research adopting the ADDIE model consisting of five stages, i.e.: analysis, design, development, implementation, and evaluation. The subject of the limited test consisted of 15 students of grade VIII.G of Public Junior High School 8 Yogyakarta. The data were collected using a product feasibility assessment sheet for material and media experts, a product practicality assessment sheet for teachers, and a product readability assessment sheet for students. The results show that the developed e-module was feasible to be used according to the material and media experts and the developed e-module is practical according to teachers and students.